PENGEMBANGAN MODUL PEMBELAJARAN IPAS BERBASIS PBL PADA MATERI INDONESIAKU KAYA BUDAYA KELAS IV SD - Ferdinandus Mau; Moh. Farid Nurul Anwar; Chusnul Chotimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low learning interest and motivation of students, which was reflected in minimal active participation and lack of attention to teacher explanations, affecting their understanding of the material and achievement of the Minimum Completeness Criteria (KKM). The study aimed to develop a Problem Based Learning (PBL)-based learning module that is valid and effective. This research employed the Research and Development (R&D) method using the Borg and Gall model, modified into seven stages: data collection, planning, product development, design validation, product revision, small-scale trial, and large-scale trial. The research subjects consisted of 31 fourth-grade students of SDN Merjosari 3. Data were collected through expert validation, teacher and student response questionnaires, and learning outcome tests. The results showed that the module was highly valid (media 96%, material 84%, language 84%). The small-scale trial indicated effectiveness of 88% with a teacher response rate of 96%, while the large-scale trial reached 90% effectiveness with a teacher response rate of 98%. The average learning outcome score of 87.84 indicated an improvement in students’ understanding. The module is considered feasible for use as it supports active, contextual, and meaningful learning.